INDONESIAN ANALYSIS SENTIMENT ON NON FUNGIBLE TOKEN (NFT) - Adhitia Erfina; Dinda Tasya Mahardika (IJNMT (International Journal of New Media Technology), 2022)
NFT or Non-Fungible Token is a unique token attached to a digital asset that is connected to the blockchain system. Various assets, digital art, music, tweeters, memes, sold as NFT, NFT has been widely discussed on various social media, one of which is Youtube. NFT has become a new trend for the Indonesian people, based on the fact that someone who sells selfie photos at the Open Sea is viral because people think it is a trivial thing but why do they produce it, but people actually accept the trend as a mistake, they intentionally upload their identity on the platform. This Open Sea, this happened because there was little information related to NFT and the public did not really understand that NFT could be a bridge for criminals. But in this case, many people as artists have been greatly helped in the marketing of their art. And even when the stock market is down, NFT remains one of the digital assets that attracts the attention of the world community, therefore this study was made to analyze the public's response with sentiment analysis, data obtained from Youtube content comments and then classified into Positive, negative, and neutral classes with TF IDF for the process of word weighting and classification using the Naïve Bayes Classifier algorithm. The test is carried out by calculating accuracy, precision, recall and F1-score, using a variety of training data and test data. And the accuracy results are 64%, for positive prediction class precision is 63%, neutral class precision is 83%, while for negative prediction is 0% and recall obtained from positive is 99%, neutral recall is 0.7% while negative is 0%. These results are the data obtained on Youtube comment